Paisajes de dependencia en Cochabamba durante el Tawantinsuyu y la colonia temprana - Gabelmann, Olga; Noack, Karoline (Pontificia Universidad Católica del Perú, 2024)
One of the major transformations of the landscape and ecosystem that the Cochabamba Valley underwent was due to the conquest by the Incas, which caused the displacement of its population and the relocation of mitimaes from all parts of Tawantinsuyu to work the newly expropriated state lands. Thus, the valley became a new centre of dependency and consolidation of the Inca state. Only shortly afterwards, the Spanish conquest, through new displacements of labour, created colonial dependencies, but based on already-existing structures, especially on the state farms. The lands themselves became the nucleus of colonial exploitation and therefore the focus of conflicts between Spaniards and indigenous people, but also between the indigenous people themselves. Our aim is to understand the intertwining of the dependencies created in the course of both conquests, which were reflected in various modifications of the landscape and ecosystem. To do so, we innovatively use combined archaeological (GIS mapping, survey, excavation) and ethnohistorical (data systematisation and toponymy) methods, so as to understand the location and use of land in the changing dependency landscapes of the Cochabamba valley from the Late Intermediate Period (1000/1100-1470 AD) to the early colonial period (1538-1700 AD).

Una de las mayores transformaciones del paisaje y del ecosistema que sufrió el valle de Cochabamba fue la conquista de los incas, que provocó el desplazamiento de su población y la reubicación de mitimaes en diversas partes del Tawantinsuyu para trabajar los campos de cultivo estatales recientemente expropiados. De esta manera, el valle se convirtió en un nuevo centro de dependencia y consolidación del Estado inca. Poco después, con la conquista española, se crearon dependencias coloniales mediante nuevos desplazamientos de mano de obra apoyados en estructuras existentes, sobre todo en las chacras estatales. Estas tierras se convirtieron en núcleos de explotación colonial y, por lo tanto, en objeto de conflictos entre españoles e indígenas, pero también entre los propios indígenas. En este artículo, nuestro objetivo es comprender los entrelazamientos de las dependencias creadas en el curso de ambas conquistas, que se reflejaron en diversas modificaciones del paisaje y del ecosistema. Para ello, y de manera innovadora, utilizamos métodos arqueológicos (mapas SIG, prospecciones y excavaciones) y etnohistóricos (sistematización de datos y topónimos) que, combinados, nos ayudarán a comprender la ubicación y el uso de tierras en los cambiantes paisajes de dependencia del valle de Cochabamba desde el Período Intermedio Tardío (1000/1100-1470 d.C.) hasta la colonia temprana (1538-1700 d.C.).
Landscapes of dependency in Cochabamba during the Tawantinsuyu and early colonial period
Keywords: Inca state; Movilization; Dependency; Qollqas; Mitimaes; Cochabamba; Estado inca; Movilización; Dependencia; Qollqas; Mitimaes; Cochabamba; https://purl.org/pe-repo/ocde/ford#6.01.02